Konsep Negara dan Demokrasi dalam Perspektif Hukum Islam dan Hukum Positif di Indonesia - Wildan, Muhammad Dimas Hidayatullah (Lembaga Yasin AlSys, 2022)
The concept of the State and democracy has spread to become an issue loaded with various meanings, so that at present it seems that almost all countries claim to be 'democratic'. The concept of the State in Islam is an organization of law and order while the State is a khilafah and imamate. In contrast to Islamic Law, positive law in Indonesia discussing the State and Democracy must be in accordance with the Pancasila Principles.